Gender pay gap in a European comparison: Positive correlation between the female labor force participation rate and the gender pay gap - Julia Schmieder; Katharina Wrohlich (DIW Weekly Report, 2021)
Public interest in the gender pay gap has risen significantly over the past years in Germany, but the size of the gender pay gap has barely changed. A comparison across European countries shows that a lower female labor force participation rate is associated with a smaller gender pay gap. The gender differences in the characteristics of the labor force, which vary across countries, are one explanation for this. Germany has one of the highest gender pay gaps in Europe compared to all countries as well as to those with a similar female labor force participation rate. With comparatively low gender pay gaps and high female labor force participation rates, the Nordic countries stand out positively in Europe. The extension of partner months in parental leave, the quantitative and qualitative expansion of child care, and a reform of joint taxation of married partners (Ehegattensplitting) are suitable instruments to achieve more gender equality on the labor market in terms of participation and wages.
Keywords: J16; J31; J21; J22; 330; gender pay gap; female labor force participation; Europe; international comparison